Palladium- and copper-catalysed heterocycle synthesis - Ball, C (2014)
A number of privileged starting materials based on aryl halide frameworks have emerged that allow access to a variety of different heterocyclic scaffolds through judicious choice of reaction conditions. This work describes efforts to develop and extend the utility of two of these general heterocycle precursors - ortho-(haloalkenyl)aryl halides A and α-(ortho-haloaryl) ketones B - in conjunction with cascade reactions involving the construction of key carbon-heteroatom bonds via palladium or copper catalysis. Chapter 1 entails an overview of the development of palladium- and copper-catalysed carbon-heteroatom bond forming processes. The application of these processes in heterocycle synthesis using ortho-(haloalkenyl)aryl halide and ortho-haloacetanilides/ α-(ortho-haloaryl) ketone precursors is also described. Chapter 2 focuses on the development of a two-step synthesis of cinnolines using ortho-(haloalkenyl)aryl halides via intermediate protected dihydrocinnoline derivatives C. Chapter 3 demonstrates how the inherent reactivity of protected dihydrocinnoline derivatives C can be harnessed to provide access to functionalised products. A brief target synthesis of a pharmaceutically-relevent cinnoline is also described. Chapter 4 details attempts to develop a novel synthesis of benzothiophenes D from both ortho-(haloalkenyl)aryl halide and α-(ortho-haloaryl) ketone precursors.